DAMPAK MANAJEMEN PEMBELAJARAN KOLABORATIF TERHADAP PENINGKATAN KOMPETENSI PROFESIONAL GURU SEKOLAH DASAR DI INDONESIA - Grasellia, Lydia; Tarigan, Revandika Adrianta; Hutagalung, Rustina; Putri, Annisa; Budimanto, Agum (Universitas Negeri Medan, 2026)
This study aims to analyze the impact of collaborative learning management on improving the professional competence of elementary school teachers in Indonesia. The method used is a literature study by reviewing previous studies from 2020 to 2025. The results of the study indicate that collaborative learning management can improve teachers' abilities in designing, implementing, and evaluating learning. Collaboration among teachers facilitates the sharing of knowledge, skills, and experiences, which has a positive impact on the quality of learning in elementary schools. The implementation of collaborative learning management involves integrated planning, implementation, and evaluation, and requires support from the principal and a conducive work environment to achieve optimal results.